Women with patellofemoral pain show changes in trunk and lower limb sagittal movements during single-leg squat and step-down tasks. - Morita, Ângela Kazue; Tavella Navega, Marcelo (Physiotherapy Theory & Practice, 2024)
Background: Changes in the trunk and lower limbs' sagittal movements may cause patellofemoral pain (PFP) because they influence the forces acting on this joint. Objectives: To compare trunk and lower limb sagittal kinematics between women with and without PFP during functional tests and to verify whether sagittal trunk kinematics are correlated with those of the knees and ankles. Methods: A total of 30 women with PFP and 30 asymptomatic women performed single-leg squat (SLS) and step-down (SD) tests and were filmed by a camera in the sagittal plane. The trunk inclination angle, forward knee displacement, and ankle angle were calculated. Results: The PFP group exhibited less trunk flexion (SLS, p =.006; SD, p =.016) and greater forward knee displacement (SLS, p =.001; SD, p =.004) than the asymptomatic group; there was no significant difference in ankle angle (SLS, p =.074; SD, p =.278). Correlation analysis revealed that decreased trunk flexion was associated with increased forward knee displacement (SLS, r = −0.439, p =.000; SD, r = −0.365, p =.004) and ankle dorsiflexion (SLS, r = −0.339, p =.008; SD, r = −0.356, p =.005). Conclusion: Women with PFP present kinematic alterations of the trunk and knee in the sagittal plane during unipodal activities. Furthermore, the trunk and lower limb sagittal movements were interdependent.